2023
DOI: 10.26418/jeep.v4i1.55203
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception toward the Use of Moodle-Reader for Improving Reading Comprehension

Abstract: This research aimed to investigate the students’ perception toward the use of Moodle-reader for improving reading comprehension. This study was descriptive research with a qualitative approach that used questionnaires and interviews. The respondents were 20 participants who were part of the member of Academic Resources Center (ARC) as students in the English Education Student Program at Universitas Tanjungpura. The researcher found that the perceptions of each student about using Moodle-reader for improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The descriptive results reveal that most of the students surveyed perceive their performance in the use of the Moodle platform as regular. This finding contrasts with Riyani et al (2023), which highlights a positive perception. Both fair and poor levels could be influenced by several factors, such as the user interface, the quality of the proposed activities or familiarity with the platform.…”
Section: Descriptive Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…The descriptive results reveal that most of the students surveyed perceive their performance in the use of the Moodle platform as regular. This finding contrasts with Riyani et al (2023), which highlights a positive perception. Both fair and poor levels could be influenced by several factors, such as the user interface, the quality of the proposed activities or familiarity with the platform.…”
Section: Descriptive Analysismentioning
confidence: 56%
“…Likewise, Riyani et al (2023) found that students had positive perceptions about Moodle and its reading tools, highlighting their usefulness, motivation and satisfaction. In the case of Meléndez & Vimos (2021), they highlighted that the strategies, such as quizzes and games, applied through the learning platforms, improve English reading comprehension.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Reading and comprehension tasks should be included in reading lessons. Reading, according to Riyani et al (2023), is about more than merely importing words and precise information from the text; it is also about the students' comprehension. Moreover, reading comprehension is learning from text in which activities should be suited to the texts and to one's reasons for reading them (Julianti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%